Energy Performance Evaluation of Domestic Airport Departure Hall TIA, Kathmandu - Shrestha, Ritu; Maharjan, Sanjeev (Journal of Advanced College of Engineering and Management, 2023)
This research focuses on the energy performance of the building envelope of an Airport Terminal Building in Kathmandu, Nepal. This study explores how to improve thermal comfort Energy analysis through a quantitative analysis of the effect of thermal characteristics of the building envelope. Development of base model Revit and duplicated in Autodesk Insight. This study is about the operational electricity consumption, Peak Heating/cooling load and Energy use intensity of the building at domestic departure hall at Tribhuvan International Airport, Building envelops systems pose a great scope to reduce the energy consumption and consequently improve building efficiency. This research is concern with reduction of operational electricity consumption on Heating and cooling system Most part of the energy consumption is occupied by HVAC system and this consumption needs to be optimized to reduce whole energy consumption of the buildings.